Early dejection of glaucoma cases by cupping disc examination (Universitas Gadjah Mada, 1987)
Two cases of glaucomas were found by papil disc examination. In the elder patient, more than 40 years old, glaucoma was diagnosed by tonometric examination. In the younger patient, less than 40 years old, suspected glaucoma was diagnosed by water drinking test. Key Words: papil disc examination - cupping disc ratio - tonometric examination - water drinking test - glaucoma